A prospective longitudinal study of postnatal dentoalveolar and palatal growth: The anatomical basis for CAD/CAM‐assisted production of cleft‐lip‐palate feeding plates. Issue 7 (30th May 2017) - Bauer, Franz X.; Güll, Florian D.; Roth, Maximilian; Ritschl, Lucas M.; Rau, Andrea; Gau, Dominik; Gruber, Maximilian; Eblenkamp, Markus; Hilmer, Bettina; Wolff, Klaus‐Dietrich; Loeffelbein, Denys J.
Abstract : This study describes the dentoalveolar and palatal growth during the first months of life. Knowledge concerning this development is essential to avoid unwanted events such as mucosal ulcerations or restriction of growth when cleft‐lip and palate (CLP) patients are treated. The results involve the generation of CAD/CAM CLP‐feeding plates. Intraoral impressions from 32 healthy newborns were taken monthly for 5 months, supplemented by measurements of body weight, length, and occipital‐frontal head circumference. The casts were digitalized, and two observers manually selected defined anatomical landmarks on virtual 3‐D models. The distances between these landmarks were evaluted. Statistical analysis included an inter‐rater agreement analysis and the determination of growth. In total, 213 casts were analyzed, with 65 models excluded because of inaccuracies in impression‐taking or cast production. Overall longitudinal growth was 20.3%, whereas transversal growth reached a maximum of 21.1%. Vertical growth was 32.4% at the tuberal level. On the basis of these results, a semiautomated series of feeding plates allowing for monthly expansion could be generated. The acquired data serve as a useful reference for other pediatric and orthofacial investigations and treatments. One such application is the automated, fully virtual manufacture of CLP‐feeding plates based on only one impression‐taking. Our data reveal when caution is needed to prevent ulceration. The series of plates generated can minimize the time‐consuming impression‐taking and the production of further plaster models. The method of measurement is suitable for documentary purposes. Clin. Anat. 30:846–854, 2017. © 2017 Wiley Periodicals, Inc.